PERAN MAHASISWA DALAM MENCEGAH DAN MENANGGULANGI BAHAYA NARKOBA MELALUI SOSIALISASI DAN AKSI BNN DI STKIP PERSADA KHATULISTIWA SINTANG - Juri, Juri; Ishabel, Surya; Putra, Alvrinaldo Yosa; Yolanda, Marsela Tifani (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2024)
Â This article discusses the role of students in preventing and overcoming the dangers of drugs through outreach and action carried out with the National Narcotics Agency (BNN). Students have great potential as agents of social change in efforts to prevent drug abuse. By organizing outreach and action with BNN, students can increase public awareness of the bad effects of drugs, as well as provide information about prevention and rehabilitation. This article also highlights the importance of collaboration between students and BNN to create a campus and community environment that is free from the dangers of drugs. Methods used First, always be alert to technological developments, sophisticated technology means that dealers can easily carry out their intentions to distribute illegal drugs. Second, set an example so that you can provide guidance and encouragement to do better. Third is caring, as well as the most important thing to prevent and eradicate drug abuse. In this case, students must be true pioneers in eradicating drugs, not just as "spectators" or even owners, distributors, dealers or users. Apart from being a propaganda machine capable of destroying untruths, students are expected to become an idealistic mass group that upholds norms and moral values, as well as being agents of change, especially in the world of education. Keywords: Prevention and control, role of students, BNN actions